Saetheria Jackson from the Sino-Indian Region (Diptera: Chironomidae) - Yan, Chuncai; Sæther, Ole A.; Wang, Xinhua (Zootaxa, 2011)
The two previously known Sino-Indian species of the genus Saetheria Jackson are reviewed. Three new species, S. glabra sp. n., S. digitata sp. n. and S. separata sp. n. are described and illustrated as males. The males of S. tylus (Townes) from Japan are re-examined. A key to known males of Saetheria is provided.